Study on the Correlation between Interleukin-27 and CXCL10 in Pulmonary Tuberculosis. (22nd June 2022) - Fan, Jiahui; Yang, Yefeng; Wang, Liang; Shang, Xiaoqian; Zhang, Li; Sun, Hu; Ma, Yujie; Li, Ying; Wang, Jing; Ma, Xiumin
Abstract : Objective . To investigate the correlation between interleukin-27 and CXCL10 and other cytokines in pulmonary tuberculosis and to further explore the related miRNAs through bioinformatics. Methods . Collect the lesion tissue and peripheral blood of pulmonary tuberculosis patients and the peripheral blood of healthy controls. Immunohistochemical staining and qRT-PCR were used to observe the expression of interleukin-27, CXCL9, CXCL10, and CXCL11. Then, predict the key miRNA, qRT-PCR was used to verify the expression of miRNA in the peripheral blood and evaluated the correlation between them. Results . Both immunohistochemical staining and qRT-PCR indicated that the expressions of IL-27, CXCL9, CXCL10, and CXCL11 were significantly increased in tuberculosis patients, and IL-27 was significantly correlated with CXCL10 (r = 0.68 ). Key molecules such as has-let-7b-5p, has-miR-30a-3p, and has-miR-320b were screened out. Among them, has-let-7b-5p was significantly downregulated, and has-miR-30a-3p was significantly upregulated; they were related to interleukin-27 and CXCL10. Conclusion . Our data shows that interleukin-27 and CXCL10 are significantly related in pulmonary tuberculosis, and has-let-7b-5p and has-miR-30a-3p are also related to interleukin-27 and CXCL10. It laid the foundation for subsequently exploiting the potential biomarkers in tuberculosis disease.